Opportunites De Financement Et Evolution Des Activites Agro-Pastorales A L#x2019;ouest Cameroun (Global Journal of Management and Business Research, 2020)
Western Cameroon has been the subject of strong changes in agricultural practices, which mainly results from the coffee decline and the economic crisis that has raged since 1985. The peasants have abandoned the cultivation of coffee to convert to other activities. For this, they needed funding; because now left to their fate. This work deals with the role of financing in the evolution of agro-pastoral activities in western Cameroon between 1989 and 2003. What are the different funding opportunities that have contributed to the evolution of agro-pastoral activity in western Cameroon during this same period?
Keywords: economic crisis; financing opportunity; agricultural activities; evolution